‘They’ve really gone to town with all that bunting’: the influence and (in)visibility of Glasgow’s Jazz Festival - Eales, Alison Caroline (Jazz Research Journal, 2014)
Glasgow International Jazz Festival has run every year since 1987, making it the city’s longest-running music festival. This article, part of an ongoing study into the Festival’s history, identifies the circumstances in which the Festival emerged and some of the organizations and individuals involved with bringing it into existence. Drawing on company records, publicity materials and press coverage, the article then argues that the Festival’s existence is dependent on an unpredictable relationship with the city of Glasgow (in terms of both its physical environment and its authorities). Glasgow’s post-industrial regeneration has been based in part on investment in cultural tourism and the infrastructure necessary to accommodate it, a strategy which the Festival has both benefited from and contributed to. In more recent years, however, weakening commitment from local authorities has seen the Festival’s influence in the city diminish and its role in the cultural life of the city become less secure.